PENGETAHUAN DAN SIKAP IBU YANG MEMPUNYAI ANAK BALITA TENTANG PENYAKIT CAMPAK - Rohaniah, Reni; Asriyani Maryam, Nenden Nur; Sukmawati, Sukmawati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
In Garut regency in 2016 has occurred 323 cases of measles extraordinary events (KLB) with 32 people died and the highest number of death is in Kersamenak Community Helath Center as many as 48 cases. An effort to prevent measles is by giving immunizations. The scope of immunization can be influenced by the knowledge and attitudes of mothers about measles immunization. The purpose of this study was to determine the description of knowledge and attitudes of mothers who have toddlers about measles in the Kersamenak Community Health Center in Garut Regency. The study design used quantitative descriptive. The population in this study was mothers who had children under five in the working area of Kersamenak Community Health Center as many as 231 mothers. The sample was taken by purposive sampling technique, the number of samples as many as 146 mothers who have toddlers. The instrument used was made by researcher with a valid test r table ? 0.514 and a reliable Cronsbach alpha test 0.944. Analysis of the data was univariate. The results showed that most of mothers has good knowledge as many as 100 people (68.5%) and almost half of th mothers have favorable attitude as many as 74 people (50.7%). It can be concluded from this research that the mother's knowledge is sufficient because they understands the meaning of measles, how to be infected by measles, signs of measles, complications of measles, prevention of measles, and care for measles. Attitude of the mothers was favorable due to the cognitive, affective and conative attitude of most mothers strongly agree with environmental hygiene, measles symptoms and information on the benefits of measles immunization. It is expected that the Community Health Center can provide more intensive information to the public about measles.